ICUs worldwide: results of a nationwide survey of Colombian intensive care units (2002)
Sixty-three of 89 identified intensive care units in Colombia (Evaluation of Intensive Care in Colombia) participated in this voluntary study. A convenience sample of 20 intensive care units, each submitting 200 patients or more, was chosen, from which the following information is presented. The Intensive Care National Audit and Research Center (UK) protocol was used to evaluate patient severity, length of stay, raw and anticipated mortality, intensive care unit patient admission/rejection criteria, and human and technologic resources available. Information was drawn from public and private institutions.